The Roman fort at Bertha, the 1973 excavation - Adamson, Helen C; Gallagher, Dennis B (Proceedings of the Society of Antiquaries of Scotland, 1987)
A small excavation revealed a single ditch with associated rampart and intervallum features. Old finds suggest Flavian and Antonine occupation. F B